International Symposium on Oilfield Chemistry 2007
DOI: 10.2118/106375-ms
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Gravitational Gradient in a Deepwater Reservoir as Determined by Downhole Fluid Analysis

Abstract: fax 01-972-952-9435. AbstractThe fluids in large reservoirs can be in equilibrium -especially if conditions conducive to convective mixing prevail. A large vertical column of reservoir hydrocarbons offers a unique laboratory to investigate potential gravitational grading. Asphaltenes are known to exist in crude oils as a colloidal suspension, but which had not been well characterized in the laboratory until recently. In this paper, we review a gravitational gradient of asphaltenes in a reservoir and a simple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…10 shows the Downhole Fluid Analysis (DFA) optical spectra acquired in situ in wells of crude oils at various locations in the Tahiti filed, deepwater Gulf of Mexico. DFA is a relatively new technology that has importance in sample acquisition (Mullins and Schroer 2000), characterization of reservoir compositional variation of equilibrated light ends (Fujisawa et al 2004;Dubost et al 2007), of equilibrated heavy ends (Mullins et al 2007a), of disequilibrium Elshahawi et al 2007), and for compartments . Fig.…”
Section: Asphaltene Nanoaggregate Clusteringmentioning
confidence: 99%
“…10 shows the Downhole Fluid Analysis (DFA) optical spectra acquired in situ in wells of crude oils at various locations in the Tahiti filed, deepwater Gulf of Mexico. DFA is a relatively new technology that has importance in sample acquisition (Mullins and Schroer 2000), characterization of reservoir compositional variation of equilibrated light ends (Fujisawa et al 2004;Dubost et al 2007), of equilibrated heavy ends (Mullins et al 2007a), of disequilibrium Elshahawi et al 2007), and for compartments . Fig.…”
Section: Asphaltene Nanoaggregate Clusteringmentioning
confidence: 99%
“…Oil Compositional Gradients. Mullins et al [3][4][5][6] suggested oil compositional gradients (i.e. asphaltene gravitational gradients) should be taken into account in the case of fields that have large structural depth.…”
Section: Conventional Explanation For Anomalous Aop Resultsmentioning
confidence: 99%
“…Downhole fluid analysis (DFA) has been successfully used to delineate reservoir attributes such as vertical and lateral connectivity and properties of the produced fluids. DFA not only measures bulk fluid properties such as the gas−oil ratio (GOR), density, and light-end compositions of CO 2 , CH 4 , C 2 H 6 , C 3 H 8 −C 5 H 12 fraction, and hexane and heavier (hexane +) fractions more accurately but also color (optical density, OD) that is linearly related to the heavy ends (asphaltenes and heavy resins) in real time at downhole conditions. In addition, the color measurement is one of the most robust measurements in DFA.…”
Section: Introductionmentioning
confidence: 99%
“…Although asphaltene gradients do not explicitly prove reservoir connectivity, the lack of an asphaltene gradient indicates a lack of connectivity. The recent advances in asphaltene science from the laboratory and field data have demonstrated that asphaltenes are dispersed and/or suspended in crude oils and/or solvents in three forms: molecules, nanoaggregates, and clusters of nanoaggregates. This provides us with a new foundation for methods of determining flow connectivity in the reservoir. In particular, in situ measurements of color (thus asphaltene content) and GOR (composition) by DFA in the reservoir enable coupling data with new thermodynamic models to determine the state of the asphaltene distribution.…”
Section: Introductionmentioning
confidence: 99%